PENGEMBANGAN MODUL PEMBELAJARAN BIOLOGI BERBASIS INTEGRASI ISLAM SAINS - Siska Arimadona (STKIP ROKANIA, 2016)
The purpose of this research is to produce valid and practical learning module in adictif and psychotropica topic. The types of this research is the development of research. The module was developed by using a four-D models. The procedure is used such as define, design, develop, and disseminate. The disseminate phase is not done because of limited time and expense in the research. Data instrument are used such as validation sheet, based on the research that has been made known the modules be valid with percentage 79,11%. Thus the quality of the products can be said to be valid by the validity of the test results of that has been done